Maintenance management program through the implementation of predictive tools and TPM as a contribution to improving energy efficiency in power plants (2015)
This paper presents an application method of a Maintenance Management Program through the implementation of predictive tools and the Total Productivity Maintenance (TPM) methodology as a contribution for the energy efficiency improvement in thermoelectric power plants. The results of the vibration analysis, lubricating oil condition and of the thermograph analysis are registered as diagnostic methods. The innovative advance in this paper was the application of four pillars from the TPM methodology at the control of the internal combustion engines efficiency at a thermoelectric power plant. This research has the objective to provide a more reliable maintenance process through the implementation of the measurement and control of the operating parameters of the plant resulting in a better management by reducing the stops due unforeseen problems. Some results of the methodology application were shown like: annual maintenance cost reduction due corrective maintenance, increase of the mean time between failure (MTBF) and reduction of the mean time to repair (MTTR) in all applied areas. These results reflected in a more reliable power generation without putting the facilities of the plant at risk with an annual cost reduction for the company.